Computer-Aided Translation in Practice - Seljan, Sanja (2003)
Today more than ever, it is impossible to imagine doing any kind of research, report or business without using computers for information retrieval and communication. As information is given on foreign language, demand for surpassing language barriers is growing every day. On one side there is general tendency to globalization, but on the other nations and international associations are trying to preserve language, tradition and cultural identity. In the situation of entering the European Union, opening global markets and multilanguage associations and companies, there is huge quantity of text to be translated on other language, so the idea of automatization in translation process could have an important role. Machine Translation or, better, Computer-Aided Translation.